UI/UX Design of a Children's Playmate Community Website using the Goal-Directed Design Method - Paramasatya, Amatya Keiko; Rudianto, Christ (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The TEBAK (Teman Bermain Anak) Community is a social organization focused on children's education through educational games. However, it currently lacks a centralized information platform that allows members and the public to easily access information about activities, programs, and community developments. The absence of an effective information medium hinders both the dissemination of information and broader community participation. This study aims to design a website interface that supports TEBAK’s efforts in information sharing and community engagement. The design process adopts the Goal-Directed Design (GDD) method, an approach in Human-Computer Interaction (HCI) that emphasizes user needs and goals. The design stages include research, modeling, requirements, refinement, and support. In the support phase, the System Usability Scale (SUS) was used to evaluate usability and user satisfaction. The testing results showed that the design received a score of 89.65 from community members and 88.55 from external stakeholders. These scores fall into the “Acceptable” category, with a Grade of “A” and an Adjective Rating of “Excellent.”